Crecimiento del cangrejo Callinectes danae (Decapoda: Portunidae) de la Isla de Margarita, Venezuela - Castillo, Jesylén (Universidad de Costa Rica, 2011)
Dana Swimming crab growth Callinectes danae (Decapoda: Portunidae) from Margarita Island, Venezuela. Callinectes danae is a common species captured with crab traps in nearby areas of coastal lagoons in Margarita Island. Although its considerable economic importance as a fishery resource, few studies have been done on population dynamics and its fishery potential in local coastal environments to support decision making in fishery administration. We present growth pattern details of Callinectes danae to better estimate its population size and exploitation feasibility. For this, we analyzed a total of 3 623 specimens that were monthly captured in crab pots by artisanal fishermen in Las Marites lagoon, from October 2007 to September 2008. The length-weight ratio was determined, and growth parameters estimated from both length and weight curves of the von Bertalanffy model. The general sex ratio showed no significant difference between males and females (?2=0.04, p > 0.05). However, values of slopes b between males and females were significantly different (ts=2.75, p < 0.05), as well as intercepts a (ts=2.44, p < 0.05). Thus, the length-weight ratio was determined separately: W=7.48e-5*L2.98 for males and W=1.21e-4*L2.87 for females, indicating a negative allometric growth in both sexes. Growth parameters were established as: L8=134.80mm, W8=166.04g and k=0.86/yr for males; L8=122.35mm, W8=118.45g and k=0.63/yr for females. Lifespan was estimated at 3.05 years for males and 4.24 years for females. We concluded that Callinectes danae is a species with short lifespan and moderately rapid growth. The coefficient of variation values (CV), of the phi-prime growth performance index (Ø’), showed a different growth pattern compared to those obtained in other regions. We propose that a management strategy will be the periodical review of the minimum capture size for fishing area, after the great variability found in growth parameters.